Immunohistochemical Profiling of Corneas With Fuchs Endothelial Corneal Dystrophy. Issue 7 (July 2017) - De Roo, An-Katrien; Janssens, Thomas; Foets, Beatrijs; van den Oord, Joost J.
Abstract : Purpose: Fuchs endothelial corneal dystrophy (FECD) is the leading indication for endothelial keratoplasty. Further insight into its pathophysiology is needed to develop alternative therapies. Methods: Sixteen genes from a previous microarray expression experiment (FECD vs. normal) were validated using immunohistochemistry on paraffin-embedded corneas (n = 6 FECD, n = 6 normal). The results were quantified manually and semiautomatically. Results: A higher percentage of corneal endothelial cells stained for alpha–smooth muscle actin (αSMA), cytokeratin 7, and superoxide dismutase 3 in FECD versus normal [odds ratios (ORs) of 60.90, 41.70, and 15.16, respectively, P < 0.001]. Dot-like staining for major histocompatibility complex, class II, DR alpha was present in FECD, but not in normal. Higher percentages of stromal cells in FECD versus normal stained for αSMA (OR = 864.26, P < 0.001), brain-derived neurotrophic factor (BDNF, OR = 6.34, P = 0.005), fibroblast growth factor 7 (FGF-7, OR = 2.76, P = 0.011), FGF-9 (OR = 5.97, P < 0.001), receptor FGFR-3 (OR = 13.90, P = < 0.001), and serum amyloid A1 (OR = 3.45, P = 0.023). Higher percentages of corneal epithelial cells stained for αSMA (OR = 2.20, P = 0.006) and BDNF (OR = 3.94, P < 0.001) in FECD versus normal. Conclusions: These results support a role for epithelial–mesenchymal transition (αSMA), oxidative stress (superoxide dismutase 3), and major histocompatibility complex, class II, DR alpha + cells with dendritic morphology in the pathophysiology of FECD. Furthermore, corneal stromal cells express trophic molecules (BDNF and FGFs) and markers of chronic inflammation (serum amyloid A1) in FECD. Abstract : Supplemental Digital Content is Available in the Text.